IMPLEMENTATION OF A CULTURE OF TOLERANCE IN STUDENTS THROUGH THE IMPLEMENTATION OF THE SCOUTING HONOR CODE - Mutiara Putri Nabila; Eti Hanifah Tamba; Nurhabibah (CV. Asry Persada Quality, 2024)
The type of research used in this research is qualitative research. The data collection techniques carried out in this research are as follows: (1) Observation (Observation documentation and traiangulation. Research results. The culture of tolerance through a code of tolerance can be carried out in several approaches, namely individual ( personal approach), group approach (interpersonal approach) and classical approach (classical approach) the presentation methods are very diverse and flexible through stories, lectures, simulation games, questions and answers, discussions and independent assignments. In short, every form of connection (communication) can be utilized in the process of cultural or cultural education